Intercellular adhesion molecule-1 (ICAM-1) expression is upregulated by thrombin in human monocytes and THP-1 cells in vitro and in pregnant subjects in vivo - Clark, Peter; Jordan, Fiona; Pearson, Charles; D.Walker, Isobel; Sattar, Naveed; Ellison, Joanne; A.Greer, Ian (Thrombosis and Haemostasis, 2003)
Monocytes play a pivotal role in both the inflammatory and coagulation responses, which may be mediated through a variety of adhesion molecules on the cell surface, including intercellular adhesion molecule-1 (ICAM-1). Monocytes also possess thrombin receptors. In the current study, we have demonstrated that thrombin can upregulate ICAM-1 mRNA and induce ICAM-1 expression on the monocyte in vitro and that, in vivo, higher monocyte ICAM-1 expression is observed in pregnancy (which is characterised by a physiological increase in thrombin generation). In pregnant subjects, a positive correlation between monocyte ICAM-1 expression and a number of markers of vascular/thrombotic disease (including blood group, acquired activated protein C resistance and non-fasting plasma triglyceride levels) was observed. We also observed a significant relationship between monocyte ICAM-1 expression and soluble plasma ICAM-1 levels, which would be consistent with a contribution of monocytic ICAM-1 to the levels of free ICAM-1 observed in plasma during pregnancy.Consistent with a role in fibrinogen binding, our preliminary in vivo results suggest that monocyte ICAM-1 expression may be a useful marker of the thrombotic/inflammatory response, although further work is required to assess the relationship of monocyte ICAM-1 expression in thrombotic disorders.
Keywords: Monocyte; ICAM-1; thrombin; pregnancy